Identifikasi Jalur Sesar Opak Berdasarkan Analisis Data Anomali Medan Magnet dan Geologi Regional Yogyakarta - Ira Maya Fathonah; Nugroho Budi Wibowo; Yoshaphat Sumardi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
This research was aimed to know the magnetic field anomaly pattern upon Opak’s fault, to identify the direction of Opak’s fault and the structure of Opak’s fault based on Geomagnetic data. It was conducted in the vicinity of Opak’s fault in Pundong sub-district, Yogyakarta. It used magnetic method which is based on rocks magnetic susceptibility. The data were taken by G-856AX Proton Precision Magnetometer (PPM) using looping method. Data analysis was done using diurnal variation and IGRF correction, reduction to pole, upward continuation and under surface structure modelling. From magnetic field anomaly analysis, it was discovered that magnetic field anomaly on Opak’s fault has -50 nT negative closure in the East, and 100 nT positive closure in the West. According to the result interpretation of 2.5D model on two slices using Mag2DC software, it can be obtained that the under surface structure of Opak’s fault consist of Young Alluvial formation, Nglanggran formation, Semilir formation, Kebo Butak formation, and Wungkal Gamping with various thickness. The location of this Opak’s fault is almost the same with the location of Opak’s fault in Yogyakarta geology map. Opak’s fault around Pundong sub-district is a normal fault directed to N 35º E. The eastern part of the fault has a relatively constant movement, while the western part is relatively moving down.